(untitled) (Medical Forum Monthly, 2021)
Objective: To study the Prevalence of Blood transfusion diseases among blood donors. Study Design: Observational study Place and Duration of Study: This study was conducted at the Department of Community Medicine & Medicine, Sialkot Medical College, Sialkot during Jan 2019 to March 2020. Materials and Methods: Four hundred individuals of both genders who consented to give blood, were taken for study of presence of pathogens causing blood borne diseases. The individuals whose age was less than 20 years, body weight less than 50 kg and hemoglobin level less than eleven point eight mg/dl were rule out from research. The Ethical Committee permission was also taken before collection of data and get publishing in the Medical Journal. The Data was analyzed for results by SPSS version 10. Results: The prevalence of donors of blood transfusion were maximum 165 (41.25%) at age group 26-30 years and minimum 12 (3.0%) at age group 41-45 years. The prevalence of donors of blood transfusion were of male were 345 (86.25%) and female 55 (13.75%). The prevalence of donors of blood transfusion were infectious diseases was maximum 9(34.61%) of HCV and minimum 1(3.84%) of HIV. The prevalence of blood donors was maximum 160(40%) of Graduate and was minimum 20(5%) of Primary education blood donors. Conclusion: Low socioeconomic conditions may lead to various blood born diseases. Lack of health education may be an important cause of dissemination of these infections. Poor economic condition prevents individuals to get costly opinions. Health education by Government may lessen the occurrence of these infections.